2019
DOI: 10.1371/journal.pone.0210000
|View full text |Cite
|
Sign up to set email alerts
|

Ground reaction force metrics are not strongly correlated with tibial bone load when running across speeds and slopes: Implications for science, sport and wearable tech

Abstract: IntroductionTibial stress fractures are a common overuse injury resulting from the accumulation of bone microdamage due to repeated loading. Researchers and wearable device developers have sought to understand or predict stress fracture risks, and other injury risks, by monitoring the ground reaction force (GRF, the force between the foot and ground), or GRF correlates (e.g., tibial shock) captured via wearable sensors. Increases in GRF metrics are typically assumed to reflect increases in loading on internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
133
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 78 publications
2
133
0
Order By: Relevance
“…One real-time feedback method is continuous feedback, which involves feedback provision without interruption. Disadvantages of continuous feedback are that it can be Running speed Increases in running speed lead to higher peak values in most biomechanical load-related variables (J. G. Hunter, Garcia, Shim, & Miller, 2019;Matijevich, Branscombe, Scott, & Zelik, 2019) and may therefore be used as a proxy of mechanical intensity. However, running technique, surface and incline may also affect the mechanical load on tissues and running speed alone does therefore likely not provide an accurate indication of tissue loading.…”
Section: Feedback Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…One real-time feedback method is continuous feedback, which involves feedback provision without interruption. Disadvantages of continuous feedback are that it can be Running speed Increases in running speed lead to higher peak values in most biomechanical load-related variables (J. G. Hunter, Garcia, Shim, & Miller, 2019;Matijevich, Branscombe, Scott, & Zelik, 2019) and may therefore be used as a proxy of mechanical intensity. However, running technique, surface and incline may also affect the mechanical load on tissues and running speed alone does therefore likely not provide an accurate indication of tissue loading.…”
Section: Feedback Frequencymentioning
confidence: 99%
“…Increases in insole pressure are often assumed to reflect increases in internal tissue loading, which is important to quantify for injury prevention. Matijevich et al (2019) recently showed that ground reaction forces do generally however not correlate well with bone (tibia) loading and only have a small contribution to bone load magnitude. Some ground reaction force metrics were even negatively correlated to bone load and may therefore even provide misleading information in some situations.…”
Section: Feedback Frequencymentioning
confidence: 99%
“…Thus, inferences and speculation about running overuse injury risks are often being made based on the wrong joint reaction force estimates, resulting in misleading or unfounded conclusions [34]. Similar issues appear to exist in figure skating as well.…”
Section: Joint Contact Forcementioning
confidence: 99%
“…The sports discussed here were given as examples, but similar confusion between net joint force vs. joint contact force exists in other disciplines as well. The danger of this misconception is exemplified by Mills et al [39] study on gymnasts landing and Matijevich et al [34] study on runners, both of which demonstrate how decreasing GRFs (or GRF metrics, such as impact peaks) can actually correspond to greater joint contact forces; thus, the wrong choice of joint reaction force construct could lead to opposite conclusions.…”
Section: Joint Contact Forcementioning
confidence: 99%
See 1 more Smart Citation